A Second Look at Memoryscapes: Community and Deindustrialization in a Different Kind of Industrial Town, Haileybury, Ontario - Hamilton, William (Ontario History, 2012)
The Haileybury was formerly a regional suburb in the wilderness for a region's industrial elite. In the face of consistent deindustrialization, however, the city is now faced with reinventing itself. Using Haileybury as a case study, this article argues that memoryscapes (specifically walking tours) must be understood as politically constructed interpretations of community and place. Like other forms of public history, tours present political arguments about themes such as community, identity and future possibilities as well as diverging perspectives. Like museums, music and art, memoryscapes are a venue of public memory though which deindustrializing places struggle with what it means to live in a place now that the industries that used to define it are closed. Consequently, these interpretations can be examined as sources to investigate the issues of community, identity, place and the politics of memory, even in non-industrial spaces and in larger regional, national or even international contexts.